The standard for program management (Project Management Institute, 2013)
"Provides a detailed understanding of program management. Updates to the Third Edition include: Program Life Cycle assigned its own chapter to provide details of the unique set of elements that make up the program management phase; Highlights the full scope of program management and clarifies the supporting processes that complete the delivery of programs in the organizational setting; More detailed definition of program management within an organization, including the fundamental differences between project, and program management"--Publisher description.